Thermo-elastic properties of bcc Mn-rich high-entropy alloy - Huang, Shuo; Dong, Zhihua; Mu, Wangzhong; Ström, Valter; Chai, Guocai; Vitos, Levente (Applied physics letters, 2020)
We report a chemically disordered solid solution, Al0.6Cr0.2MnFe0.5Co0.3Ni0.5, based on a body-centered cubic underlying lattice with the measured Curie temperature of ∼380 K. First-principles alloy theory is employed to investigate the temperature-dependent free energy, elastic constants, and coefficient of thermal expansion at the ferromagnetic and paramagnetic states. Theory and experiment are found to strengthen each other, and the results indicate that the magnetic state has a strong impact on the thermo-elastic properties of the considered alloy. The present advance in the thermo-magneto-elasticity enhances the understanding required for controlling the magnetic and mechanical response of multi-component systems.